Política e esporte : a construção da ultradireita no interior do Palmeiras e a dialética da resistência - Carvalho, Emiliano Peggion de (2020)
The present work intends to elaborate an analysis about the relationship between football and politics, focusing on episodes recorded in the years 2018 and 2019. We present how the sport was used by the then candidate for President of the Republic, Jair Messias Bolsonaro, and how he approached from the board of Sociedade Esportiva Palmeiras, having actively participated in the games, as well as winning the 2018 Brazilian title, including being on the field to receive the champion cup. At the same time, it is intended to reflect on how the fans positioned themselves in the face of such attitudes, giving greater focus to dissident organizations entitled "Palmeiras Antifascista" and "Palmeiras Conservador". The work was divided into three chapters, dealing with the first about the concept of fascism and ideology. Later, in the second chapter, we dealt with the history of the relationship between politics and sport, as well as the effectiveness of this relationship in contemporary times. Finally, the relationship between the directors of Palmeiras and their organized counterparts and in favor of Bolsonaro, presenting public perspectives on social networks and the media in general. The research will have as methodological north the historical-dialectical materialism, relying on bibliographies in the critical area of sociology of sport such as Wisnik (2013), Franco Júnior (2007), Mejía (2018), Sigoli (2008), Toledo (2000); DaMatta (1994) and Araújo (2019), using as an empirical material the Facebook page of the Palmeiras Antifascist crowd, the Twitter profile of the Palmeiras Conservative crowd, and several news portals such as El País, Época, Folha de S. Paulo, Ludopédio, O Globo, Terra, Diary of the Center of the World, Clarín, Carta Capital, Vice, Veja, Lance !, A Cidade On, Gazeta do Povo and Exame. All this in order to demonstrate the relationship between football and politics and the implications within the organized fans. Our main objective is to try to answer if there was and still is a relationship between sport and politics with a focus on the relationship between the directors of Palmeiras and the candidate and future president of the Republic Jair Bolsonaro, as well as if there was the rise of an ultra-right and a kind of diffuse fascism in the country. Finally, how these relationships affected the fans.